Imprinting Sensor Based on Honeycomb Graphene Oxide for the Determination of Echinacoside in Complex Samples. Issue 1 (1st January 2023) - Ma, Jing; Wang, YanPing; Zhu, Xiumei; Cui, Fang; Li, Yuanyuan; Zhang-Peng, Xinru; Wang, Zixia; Hu, Fangdi; Shi, Xiaofeng
Abstract : Echinacoside(ECH) is a phenylethanoid glycoside compound with various pharmacological activity in Chinese medicine. The development of convenient, efficient and sensitive analysis methods for ECH in complex samples in vitro and in vivo has considerable application value. In this study, honeycomb graphene oxide (H-GO) with highly conductivity and nanoscale defect-like structure was successfully prepared by combustion method. It was used as a modified material for flexible electrode (ITO-PET), and then activated in alkaline solution to construct a nanomaterial modified electrode (aH-GO/ITO-PET). The imprinted sensor (MIP/aH-GO/ITO-PET) was further constructed by simple electropolymerization and elution. Under optimized conditions, the sensor achieves sensitive detection of ECH in a wide linear range of 0.1 ∼ 100 μ M, with a detection limit as low as 1.6 nM (S/N = 3), and has good repeatability, stability and anti-interference. It has been successfully used for the direct detection of ECH in Cistanche deserticola Ma wine and rat plasma.